Formulasi Sediaan Masker Peel off dari Ekstrak Buah Batok Aceh (Limonia Acidissima L.) Sebagai Pencerah Kulit - Mukhlisa, Ida; Riska, Riska; Mardiana, Rosa; Yusrawati, Yusrawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Batok fruit or known as Limonia acidissima is a fruit commonly found in South and Southeast Asia, with content that has the potential to provide benefits for skin health. Batok fruit contains many antioxidants that can improve skin brightness. This study aims to formulate and evaluate the physical characteristics of peel-off mask preparations to brighten the skin containing Aceh batok fruit extract (Limonia acidissima). The extract was obtained by maceration method using 96% ethanol solvent. The mask preparations were made in four formulations: F0 as a base without extract, and F1, F2, and F3 with extract concentrations of 10%, 20%, and 30%, respectively. Evaluation of the quality of the preparations included organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesion, drying time, and irritation test. The results showed that the addition of the extract affected the color of the preparation from yellow to yellowish brown and gave the extract a distinctive aroma. All formulas were proven safe, with pH values ​​within the physiological range of the skin (6.2-6.4) and did not irritate the panelists' skin. The drying time for all formulas was uniform, at 15 minutes. Formula F3 (30% extract) demonstrated the best spreadability (4.5 cm) compared to the other formulas. However, all formulas showed inhomogeneous results and had adhesion below the ideal standard for topical preparations, which is less than 2 seconds. It was concluded that formula F3 was the most optimal among those tested because it had the best spreadability, did not cause irritation, and improved skin brightness after washing for 1 week. However, further research is needed to improve the homogeneity and adhesion of the formulations.